Comparison of Somatic, Auditory, Visual, and Intellectual Learning Models and Snowballing Against Numerical Ability of Students - Irwanto, M Zain; Rohman, Prabu; Mahfuzh, Mahfuzh; Rozikin, Ahmad; Sriyakul, Thanaporn (Universitas Islam Negeri Raden Intan Lampung, 2020)
Numerical ability in learning mathematics is an important thing for students to facilitate teaching and learning process. SAVI and SNAWBALLING are learning models that can facilitate the development of numerical abilities of students. The purpose of this study is to determine the effect of SAVI and SNOWBALLING learning models on the numerical ability of students. This research is a type of research Quasy Experimental Design. The sampling technique used was class random technique with row and series material. The instrument used to collect data was a numerical ability test in the form of a description item. The data analysis technique of this study used the T-Test analysis technique. The results of this study are that the two models do not have the same numerical ability of students, meaning that there are differences in the impact given by the SAVI learning model and the SNOWBALLING learning model on numerical ability. The numerical ability of students using the SAVI learning model is better than using the SNOWBALLING learning model.